HUBUNGAN MALNUTRISI DAN JENIS PENYAKIT DENGANLAMA RAWAT INAP PADA LANSIA DI RSUP FATMAWATIPERIODE 2018 - Alfian Zulhakim (2020)
Malnutrition is a common problem in geriatric patients. This situation can occur because food intake is less than food outake and unbalance nutrition intake. Poor nutritional status can directly increase the length of stay. The indirect relationship between poor nutritional status and length of stay can be explained through a decrease in body immunity, psychological stress, impaired body functions, and an increased risk of complications and infection. The purpose of this study was to determine the relationship of malnutrition and type of disease with length of stay. This research method was analytic observational with cross-sectional design and using chi-square as a statistical test. The sampling technique used simple random sampling which based on inclusion criteria with a minimum sample size of 77. This study showed there was significant association between nutritional status (p = 0.032) and type of disease (p = 0.016) with length of stay. The length of stay of patient was greatly influenced by the nutritional status of the patient and the type of illness the patient was suffering from.